ANALYSIS OF BEEF INVENTORY PLANNING WITH APPROACH MONTE CARLO METHOD IN CV. PUTRA SURYA - Ahmad Sauqi (MBA - Journal of Management and Business Aplication, 2020)
Research with the title Analysis of Planning Beef Inventory with Monte Carlo Method Approach in CV. Putra Surya was held for 3 months, from September to November 2019. The data used in this research is secondary data obtained from the owner of CV. Putra Surya. Based on the results of the analysis that hasbeen done with Monte Carlo Simulation, CV. Putra Surya can plan beef supply for 2020 of 35,388 kg of beef with an average demand in one week of 707.76 kg. For expected requests or expected values of 704.96. The average demand that has been processed by the Monte Carlo Simulation method of 707.76 kg per week is not too different from the expected demand of 704.96 kg per week. There is a difference of 2.8 kg between the simulation value and the expected value and this difference can be influenced by the number of tests or experiments conducted. Keywords:Inventory, Supplay,Demand,Monte Carlo